FERNANDES, Florestan — O Desafio Educacional. São Paulo: Cortez, 1989. - Soares, Eliane Veras (Sociedade e Estado, 2022)
resenha da obra: FERNANDES, Florestan — O Desafio Educacional. São Paulo: Cortez, 1989.